2009
DOI: 10.1111/j.1365-3148.2009.00918.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of red‐cell concentrates in SAG‐M filtered through the MacoPharma™ P‐CAPT prion‐reduction filter

Abstract: This study investigated whether filtration of leucodepleted red cells in SAG-M through the P-CAPT filter in order to prevent the potential risk of vCJD infection associated with prion transmission through transfusion has any deleterious effect on red-cell quality. Bottom-and-top SAG-M leucodepleted red-cell concentrates (24 units) were prion-reduction filtered on the day following collection, with half of the units undergoing irradiation on day 14. A control group (12 units) was not prion filtered. Units were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
(26 reference statements)
2
15
0
Order By: Relevance
“…In line with a number of smaller studies (Murphy et al, 2009;Cancelas et al, 2011) we found that transfusion of PF-RCC did not result in increased immunogenicity or other significant complications in patients. In addition, we demonstrated that alloimmunization rates in surgical patients, irrespective of study arm, were similar to previous reports (Redman et al, 1996).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with a number of smaller studies (Murphy et al, 2009;Cancelas et al, 2011) we found that transfusion of PF-RCC did not result in increased immunogenicity or other significant complications in patients. In addition, we demonstrated that alloimmunization rates in surgical patients, irrespective of study arm, were similar to previous reports (Redman et al, 1996).…”
Section: Discussionsupporting
confidence: 89%
“…P-Capt filtered red blood cell concentrates (PF-RCC) behaved normally in laboratory assays and had a normal antigenic profile (Murphy et al, 2009), and a study in 20 patients showed that exposure to 1-2 PF-RCC units did not generate any attributable adverse events (Cahill et al, 2010).…”
mentioning
confidence: 99%
“…The resin also demonstrated the ability to remove endogenous infectivity from hamster leukoreduced RBCs to below the limit of detection of the bioassay used to determine the infectivity titer 11 . RBC storage variables after leukoreduced RBCs were filtered with the P‐Capt prion filter and then stored with either plasma‐CPD or SAGM to outdate have been evaluated 16‐18 . All of the final variables (hemoglobin [Hb] g/unit, hematocrit [Hct], residual WBCs, total volume) as well as end of shelf life product variables (hemolysis, adenosine 5′‐triphosphate [ATP], 2,3‐diphosphoglycerate acid [2,3‐DPG], potassium, and pH) were within the UK and Council of Europe Guidelines 19,20 .…”
mentioning
confidence: 99%
“…All of these cases occurred in the United Kingdom before the introduction of universal leukoreduction of RBCs. The high incidence of vCJD in Ireland has raised concerns that there may be a significant risk of secondary transmission through infected blood products 6 …”
mentioning
confidence: 99%
“…The use of such filters would complement existing measures adopted to contain the risk of transmission. Although prion‐removing filters may alter the composition of RBCs that are passed through them, the resulting RBCs are considered safe for transfusion 6,10 . The aim of this study was to evaluate the cost‐effectiveness of implementing a policy of prion filtration of RBCs in the Republic of Ireland.…”
mentioning
confidence: 99%